Attitude toward genetic testing for cancer risk in Istanbul - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 2004)
To identify attitudes toward genetic testing, and the effects of this information on decisions regarding issues such as pregnancy, abortion, and prophylactic surgery, several subsets of the Turkish Population were surveyed in hospital settings. Individuals (n = 179) chosen arbitrarily from four different subsets of a Turkish population were asked to participate in a confidential 23-question survey. Survey participants were familiar with the concept of cancer being a familial disease (85.5%), and 84.7% of them expressed interest in genetic testing to determine cancer risk, 83.9% would have their fetuses tested for such cancer risk, 65.1% would terminate their pregnancies, 92.2% would have their children tested if they were determined to have an increased cancer risk, 71.9% would agree to undergo prophylactic oophorectomy or orchiectomy and 67.6% would have mastectomy/prostatectomy should there be an increased cancer risk to these organs.. It appears that at least the sampled segment of a Turkish population is willing to undergo genetic testing to determine if they are at increased risk for cancer. The feasibility and acceptance of genetic testing and the influence of education and genetic counseling in the Turkish people should further be evaluated with a larger stratified sample of the population.
Keywords: GENERAL-POPULATION; RELATIVES